7D.05: MATERNAL OBESITY ATTENUATES THE ANTI-CONTRACTILE EFFECT OF PERIVASCULAR ADIPOSE TISSUE IN OFFSPRING. (June 2015) - Zaborska, K.; Austin, C.; Wareing, M.; Edwards, G.
Abstract : Objective: Maternal obesity pre-programmes offspring to develop obesity, glucose intolerance and associated cardiovascular disease later in life although the underlying mechanism is currently unknown. This study investigated the effect of a maternal high fat diet on endothelial and perivascular adipose tissue (PVAT) regulation of resistance artery tone. Design and method: 8 week old female SD rats were fed a 10% fat diet (controls) or 45% fat obesogenic diet (HFD) for 12 weeks before mating then continued on their respective diets during pregnancy and lactation. PVAT-intact or -denuded mesenteric arteries from dams and pups (250–300 μm internal diameter) were mounted on a wire myograph. Cumulative concentration-response curves were constructed to thromboxane A2 receptor agonist U46619 (10nM-3 μM) ± 10 μM A769662, an activator of AMP-activated kinase (AMPK), and/or 100 μM L-NMMA, a nitric oxide synthase (NOS) inhibitor. Results: Body weight (BW) and systolic (SBP) and diastolic (DBP) blood pressure were significantly increased in HFD dams (BW: p < 0.05, SBP: p < 0.001, DBP: p < 0.01) and their offspring at 24 weeks (BW < 0.0001, SBP: p < 0.0001, DBP: p < 0.0001) compared to controls but no differences were observed in offspring at 12 weeks. PVAT exerted an anti-contractile effect in artery segments from control dams and their offspring at 12 and 24 weeks (p < 0.01, p < 0.001, p < 0.05), an effect which was lost in both dams fed HFD and their offspring. AMPK activation decreased contractility of both PVAT-denuded and intact control vessels in the presence and absence of a NOS inhibitor in control dams (p < 0.0001) and their offspring (p < 0.0001); this effect was decreased in PVAT-intact vessels of HFD dams and their offspring. Conclusions: In summary, the attenuated anti-contractile effects of PVAT in HFD dams and their offspring may be modulated by AMPK; however it is not totally dependent on nitric oxide release.